2014
DOI: 10.2110/jsr.2013.85
|View full text |Cite
|
Sign up to set email alerts
|

Root Calcretes and Uranium-Bearing Silcretes At Sedimentary Discontinuities In the Miocene of the Madrid Basin (Toledo, Spain)

Abstract: This paper reports a detailed study of the calcrete and silcrete profiles in the Miocene detrital deposits in the western area of Madrid, at the boundary of two main sedimentary units. The aims of this work were to better understand the pedogenic and diagenetic environments in which these profiles formed and to determine the cause(s) of their enrichment in uranium. Calcrete and silcrete duricrusts are characteristic features of closed continental basins in semiarid climates; this paper discusses the significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 77 publications
0
5
1
2
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 In the samples, U correlates positively with the CaO content and negatively with SiO2. These correlations are the opposite of those that Bustillo et al (2013) found in the geochemical composition of silicifications in silcrete in the Madrid Basin. According to these authors, U would not have been originally located in the carbonates but would be associated with the siliceous phases that replaced them.…”
Section: Uranium Contentcontrasting
confidence: 94%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 In the samples, U correlates positively with the CaO content and negatively with SiO2. These correlations are the opposite of those that Bustillo et al (2013) found in the geochemical composition of silicifications in silcrete in the Madrid Basin. According to these authors, U would not have been originally located in the carbonates but would be associated with the siliceous phases that replaced them.…”
Section: Uranium Contentcontrasting
confidence: 94%
“…The silicification proceeded in a vadose zone unfavourable for deep groundwater circulation (Głazek 1989;Głazek et al 1992;cf. Thiry and Milnes 1991;Dixon and McLaren 2009;Bustillo et al 2013) as an effect of descending solutions enriched in dissolved silica. This silica presumably originated from long-lasting (Thiry 1999) leaching of opal (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both the composition and geochemistry of the siliceous precipitates from the Sokole Hills (Table 1) are incompatible with typical pedogenic silcretes, which show a high TiO 2 content (cf. Milnes and Thiry 1992;Thiry and Simon-Coinçon 1996;Nash et al 1998;Ullyot and Nash 2006;Tofalo and Pazos 2010;Bustillo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These horizons are probably the previous stages of the formation of the massive horizons with the increasing of carbonate precipitation as indicated by the preservation of clays within the groundmass (micriteclay groundmass). The presence of root and insect traces as well as the grilled-structure (Bustillo et al, 2013) outline the significance of biogenic processes in the formation of these horizons but the displacement and strong corrosion of some grains, and the presence of some spar cements point also to non-biogenic processes (Braithwaite, 1989).…”
Section: Calcrete Profiles Interpretationmentioning
confidence: 96%